2016
DOI: 10.1017/s0033291716000258
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of executive functioning in ecstasy/polydrug users

Abstract: Ecstasy/3,4-methylenedioxymethamphetamine (MDMA) use is proposed to cause damage to serotonergic (5-HT) axons in humans. Therefore, users should show deficits in cognitive processes that rely on serotonin-rich, prefrontal areas of the brain. However, there is inconsistency in findings to support this hypothesis. The aim of the current study was to examine deficits in executive functioning in ecstasy users compared with controls using meta-analysis. We identified k = 39 studies, contributing 89 effect sizes, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 86 publications
2
18
1
Order By: Relevance
“…For primary MDMA users, we did not find any significant results in the domains of executive functions and attention except for the RAVLT parameter recall consistency, which contrasts with previous studies that found executive function and decision-making impairments in MDMA users (Fisk and Montgomery, 2009;Fisk et al, 2004;Montgomery et al, 2005;Quednow et al, 2007;Roberts et al, 2016a vary regarding attentional performance of MDMA users, which is also reflected in our results; in all three parameters measuring attention, the polydrug MDMA users performed significantly worse than controls with moderate effect sizes, whereas primary MDMA users did not differ substantially from controls. These results are in line with previous research as 1) stimulant users were shown to perform worse than drug-naïve controls in an equally created attention domain (Vonmoos et al, 2013), and 2)…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For primary MDMA users, we did not find any significant results in the domains of executive functions and attention except for the RAVLT parameter recall consistency, which contrasts with previous studies that found executive function and decision-making impairments in MDMA users (Fisk and Montgomery, 2009;Fisk et al, 2004;Montgomery et al, 2005;Quednow et al, 2007;Roberts et al, 2016a vary regarding attentional performance of MDMA users, which is also reflected in our results; in all three parameters measuring attention, the polydrug MDMA users performed significantly worse than controls with moderate effect sizes, whereas primary MDMA users did not differ substantially from controls. These results are in line with previous research as 1) stimulant users were shown to perform worse than drug-naïve controls in an equally created attention domain (Vonmoos et al, 2013), and 2)…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a meta-analytic review, Kalechstein (2007) reported only small to moderate effect sizes for attention/concentration deficits in MDMA users compared to matched controls. For executive functions, a recent meta-analysis by Roberts et al (2016a) investigated four components of executive functions: inhibition, switching, updating (Miyake et al, 2000), and access (Fisk and Sharp, 2004) and found that -compared to non-MDMA polydrug using controls -polydrug MDMA users display significant alterations with a small effect size in all functions with exception of the unaffected inhibition component. However, the authors state that they cannot rule out the possibility that concomitant drug use contributed to the deficits found in executive functioning of the polydrug MDMA users.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of shared genetic factors between parental SUD and offspring cognition are compatible with a large body of previous research showing that lower cognitive function predicts the development of SUD . Compared to healthy controls, individuals suffering from SUD exhibit a wide array of cognitive deficits . Our results add a further important dimension to this body of literature by demonstrating that the associations found in previous studies can, to a substantial degree, be explained by genetic factors and not caused only by toxic effects of substance intake.…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive ability is one of the most well‐studied phenotypes in quantitative behavioural genetics, and repeated studies using different assessment methods have shown heritability estimates typically 50% or higher . Patients suffering from SUD across all substances of abuse exhibit a wide range of cognitive deficits , which contributes to progression of the disease and affects attrition to treatment. Even though substance intake in itself causes acute cognitive deficits , reduced cognitive ability in adolescence and young adulthood is also known to predict the development of SUD , and this association is partly explained by shared genetic factors .…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] MDMA causes prolonged toxic effects on the nerve terminals Serotonergic and more recently, has been shown to reduce the number of gamma-aminobutyric acid neurons in the hippocampus of rats. [5,6] In recent decades, several molecular imaging studies directly examined in vivo the effects of ecstasy / MDMA in neurotransmitter systems. [7] An NT is a chemical released selectively from a nerve ending by the action of an action potential, which interacts with a specific receptor in an adjacent structure and which, if received in sufficient quantity, produces a certain physiological response.…”
Section: Introductionmentioning
confidence: 99%